Pengaruh Pasar Saham Terhadap Perekonomian di Indonesia - Aji Ramadhan, Satria; Ammar Zhafran; Helfira Citra (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2024)
The stock market is an important component of the financial system in Indonesia. The stock market has a significant role in influencing the country's economy, because it can facilitate capital movements and influence share prices. This research aims to analyze the influence of the stock market on the economy in Indonesia. The research method used is multiple linear regression analysis. The research results show that the stock market has a significant influence on the economy in Indonesia.